2015
DOI: 10.1142/s0218202515400096
|View full text |Cite
|
Sign up to set email alerts
|

Residual-based turbulence models and arbitrary Lagrangian–Eulerian framework for free surface flows

Abstract: Communicated by K. TakizawaWe present a residual-based turbulence model for problems with free surfaces. The method is derived based on variational multiscale ideas that assume a decomposition of the solution fields into overlapping scales that are termed as coarse and fine scales. The fine scales are further split hierarchically into fine-scales level-I and fine-scales level-II. The hierarchical variational problems that govern the two fine-scale components are modeled employing bubble functions approach. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To ensure global conservation of mass for higher Reynolds number flows, a least-squares form of local mass conservation was also imposed. Subsequently, hierarchical application of the notion of scale separation resulted in the three-level VMS method [24][25][26] which facilitated a more flexible fine-scale subsystem to derive closed form expressions for the turbulence models. In this method the fine scale pressure field that emanates from the mixed form of fine-scale variational equations helps with the conservation of mass in highly turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To ensure global conservation of mass for higher Reynolds number flows, a least-squares form of local mass conservation was also imposed. Subsequently, hierarchical application of the notion of scale separation resulted in the three-level VMS method [24][25][26] which facilitated a more flexible fine-scale subsystem to derive closed form expressions for the turbulence models. In this method the fine scale pressure field that emanates from the mixed form of fine-scale variational equations helps with the conservation of mass in highly turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier works by the senior author it was shown that variationally derived fine scale models that provide a mechanism to transfer energy between resolved and unresolved scales also satisfy the governing momentum balance equations. [23][24][25][26] The magnitude of the fine scales is dictated by the residual of the Euler-Lagrange equations of the resolved coarse scales and therefore the resulting numerical method is variationally consistent. From the modeling perspective the fine-scale variational equation provides a mathematical zoom to focus on the finer features in the flow physics, and an application of ideas from the residual-free bubbles (RFB) method directly to the fine-scale variational equation provides an opportunity that can be exploited to derive the residual-based turbulence models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The free-surface topological changes can be automatically handled by solving an additional scalar partial differential equation. Interface capturing methods have been widely applied to a wide range of interfacial problems, including bubble dynamics [17][18][19], jet atomization [20], and free-surface flows [21,22].…”
Section: Introductionmentioning
confidence: 99%